Increased cardiac fatty acid oxidation in a mouse model with decreased malonyl-CoA sensitivity of CPT1B. Issue 10 (9th April 2018) - van Weeghel, Michel; Abdurrachim, Desiree; Nederlof, Rianne; Argmann, Carmen A; Houtkooper, Riekelt H; Hagen, Jacob; Nabben, Miranda; Denis, Simone; Ciapaite, Jolita; Kolwicz, Stephen C; Lopaschuk, Gary D; Auwerx, Johan; et al.
Abstract: Aims: Mitochondrial fatty acid oxidation (FAO) is an important energy provider for cardiac work and changes in cardiac substrate preference are associated with different heart diseases. Carnitine palmitoyltransferase 1B (CPT1B) is thought to perform the rate limiting enzyme step in FAO and is inhibited by malonyl-CoA. The role of CPT1B in cardiac metabolism has been addressed by inhibiting or decreasing CPT1B protein or after modulation of tissue malonyl-CoA metabolism. We assessed the role of CPT1B malonyl-CoA sensitivity in cardiac metabolism. Methods and results: We generated and characterized a knock in mouse model expressing the CPT1B E3A mutant enzyme, which has reduced sensitivity to malonyl-CoA. In isolated perfused hearts, FAO was 1.9-fold higher in Cpt1b E3A/E3A hearts compared with Cpt1b WT/WT hearts. Metabolomic, proteomic and transcriptomic analysis showed increased levels of malonylcarnitine, decreased concentration of CPT1B protein and a small but coordinated downregulation of the mRNA expression of genes involved in FAO in Cpt1b E3A/E3A hearts, all of which aim to limit FAO. In vivo assessment of cardiac function revealed only minor changes, cardiac hypertrophy was absent and histological analysis did not reveal fibrosis. Conclusions: Malonyl-CoA-dependent inhibition of CPT1B plays a crucial role in regulating FAO rate in the heart. Chronic elevation of FAO has a relatively subtle impact on cardiac function at least under baseline conditions.